PEMBERIAN KOMPOS TKKS DAN PUPUK N, P, K PADA TANAMAN BAWANG MERAH (Allium ascalonicum L.) - Anas, Anwar; Yetti, Husna; Amri, Al Ikhsan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to determine the effect of dosage compost TKKS and ZA, TSP, KCl fertilizer on the growth and production of shallots. This research was conducted in experimental garden of Faculty of Agriculture Universitas Riau, Tampan, Pekanbaru in October - December 2015. The design used in this research is arranged in Factorial Random Design (RAK) Factorial consisting of 2 factors with 3 replications. Factor I: compost TKKS (C) with 4 doses (ton / ha) ie C1 (10), C2 (15), C3 (20), C4 (25) and factor II: ZA, TSP, KCl (K) With 3 doses (kg / ha): K0 (0), K1 (250 kg ZA / ha + 150 kg TSP / ha + 100 kg KCl / ha), K2 (500kg ZA / ha + 300kg TSP / ha + 200 kg KCl / ha). The data obtained were analyzed using multipurpose test with Duncan multiple test at 5% level. Compost TKKS and ZA, TSP, KCl fertilizer had significant effect on tuber diameter per sample clump, tuber weight per plot, and tuber weight per plot, Not significant to plant height and number of tubers per sample clump. The compost of TKKS 1.5 kg / plot was added ZA50 g / plot, TSP 30 g / plot and KCl 20 g / plot resulted in the highest onion production of 487.67 g / plot or equal to 4,8767 ton / ha compared with other treatment.Keywords: TKKS compost, ZA Fertilizer, TSP, KCl, Growth and Red Onion Production